Avaliação da resistência em caprinos a ninfas do carrapato Amblyomma cajennense (Fabricius, 1787) e da reatividade cruzada com A. hebraeum (Koch, 1844) (Acari:Ixodidae) - Monteiro, Gaby Ermelindo Roberto [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
No presente estudo avaliou-se o desenvolvimento de resistência a ninfas do ixodídeo Amblyomma cajennense, induzida por infestações controladas, e a possível existência de reatividade cruzada com Amblyomma hebraeum. Para tal, caprinos sem contato prévio com carrapatos, com seis meses de idade, machos ou fêmeas, foram infestados três vezes sucessivamente com ninfas de A. cajennense. Ademais, outro grupo de caprinos foi infestado nas mesmas condições com ninfas de A. hebraeum e colhidos soros para pesquisa de possível reatividade cruzada com A. cajennense. Observou-se que caprinos desenvolveram resistência apenas parcial a ninfas de A. cajennense, como demonstrado pela alteração significativa dos seguintes parâmetros biológicos das ninfas, em relação à primoinfestação: redução de 41,7% e 37,1% no peso de ingurgitamento, respectivamente na 2ª e 3ª infestações; aumento de 20% no período de ecdise e redução de 25,7% na taxa de ecdise, respectivamente nas 3ª e 2ª infestações. Não houve alteração no período de ingurgitamento nem na porcentagem de recuperação de ninfas com as infestações sucessivas. A reação cutânea induzida pelas ninfas de A. cajennense durante as infestações em caprinos caracterizou-se por infiltrado de células inflamatórias, predominantemente neutrófilos e basófilos, estas últimas envolvidas na imunidade a carrapatos por meio de hipersensibilidade basofílica cutânea. Células apresentadoras de antígeno, nomeadamente macrófagos, linfócitos B e células dendríticas foram detectadas por imunoistoquímica em linfonodos drenantes de locais de fixação dos carrapatos, em maior número nos linfonodos dos animais infestados...

This study evaluated the acquision of resistance against Amblyomma cajennense nymphs in naïve goats, induced by repeated and controlled infestations, and a possible cross-reactivity with A. hebraeum. Ten naive goats, of both sexes, aged six months were used throughout the experiment. Animals were infested artificially thrice, 30 days intervals between infestations. In addition, goats were infested at same conditions with the tick A. hebraeum as well. Sera from these animals were collected looking for possible cross-reactivity between antigens from these ixodids. It was observed that goats developed partially resistance to A. cajennense nymphs from the 1st infestation on as shown by changes in some biological parameters, as follows: increase of 41.7% and 37.1% in engorgement weight, respectively at the 2nd and 3rd infestations, decrease in 25.7% in nymph s ecdise rate and increase of 20% in ecdise period, respectively at the 3rd and 2nd infestations. It was not observed alterations in engorgement period and percentage of yielded nymphs. Biopsies of tick bite lesions induced by A. cajennense nymphs during infestations in goats were characterized by inflammatory reaction with cellular influx by neutrophils and basophils predominantly, being the last one involved in the well-known cutaneous basophilia. Antigen presenting cells like macrophages, B-lymphocytes and dendritic cells were detected by immunohistochemical analysis of lymph nodes draining tick infested areas. It should be stressed that these cells were found in higher numbers at lymph nodes from infested goats than from the naïve ones. Western blotting analysis of nymphal A. cajennense extracts revealed shared polypeptides (160, 90 and 16kDa) when used sera from goats infested with A. cajennense either A. hebraeum, indicating cross reactivity between these two tick species.
Keywords: Amblyomma cajennense; Caprino; Amblyomma hebraeum; Nymphs; Goat; Cross reactivity